A Qualitative Exploration of Satisfaction with Mental Health Services in Western Australia Among Sexuality and Gender Diverse Youth - Lim, Bruce Anthony (Curtin University, 2024)
The higher prevalence of clinically significant psychological distress among sexuality and/or gender diverse youth (SGD-Y) relative to youth overall, is compounded by SGD-Y’s inadequate access to professional mental healthcare. Given the unique geography and healthcare infrastructure of Western Australia, and the state government’s aim to improve health service access for SGD-Y, this research explored perspectives of 13 urban and regional SGD-Y in Western Australia, regarding their service experiences and factors linked to access and satisfaction.